2016
DOI: 10.5713/ajas.16.0024
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of indigenous cattle genetic resources in Southern Africa’s smallholder areas: turning threats into opportunities — A review

Abstract: The current review focuses on characterization and conservation efforts vital for the development of breeding programmes for indigenous beef cattle genetic resources in Southern Africa. Indigenous African cattle breeds were identified and characterized using information from refereed journals, conference papers and research reports. Results of this current review reviewed that smallholder beef cattle production in Southern Africa is extensive and dominated by indigenous beef cattle strains adaptable to the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 102 publications
3
110
0
Order By: Relevance
“…Many researchers have observed that cattle provide a variety of goods and services that generate income, ensure food security, and support smallholder rural livelihoods (Nyamushamba et al, 2017;Wilson, 2009). In Rwanda, Hirwa et al (2017) reported seven major reasons for keeping cattle among smallholder farmersmeat, income, savings, conservation, beauty/aesthetics, milk and cultural uses.…”
Section: Production Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…Many researchers have observed that cattle provide a variety of goods and services that generate income, ensure food security, and support smallholder rural livelihoods (Nyamushamba et al, 2017;Wilson, 2009). In Rwanda, Hirwa et al (2017) reported seven major reasons for keeping cattle among smallholder farmersmeat, income, savings, conservation, beauty/aesthetics, milk and cultural uses.…”
Section: Production Featuresmentioning
confidence: 99%
“…These breeds have demonstrated superior performance in fertility, reproduction, hardiness, survivability and climatic stress resistance traits over their exotic counterparts under prevailing environmental and management conditions (d'Hotman and Hatendi, 1998;Moyo, 1997). The peculiarity of these local breeds is also perceptible in higher heat tolerance, resistance to local disease epidemics, ticks and tick borne diseases, as well as improved and diversified production ability, making them better adapted to survive and tolerate harsh environments (Nyamushamba et al, 2017;Hirwa et al, 2017). They are therefore not only acclimatised to their habitat but also fit for their purpose (Wilson, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations